IMPLEMENTASI PROFIL PELAJAR PANCASILA TEMA “GAYA HIDUP BERKELANJUTAN” SISWA KELAS IV SDN LAMPER KIDUL 01 KOTA SEMARANG - Ria Indrawati; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education is one of the key factors in creating a capable and competitive generation. In the context of Indonesian education, there are ongoing efforts to improve the quality of learning and develop learners who are independent and able to face future challenges. One of the latest efforts is to develop a P5 standalone curriculum that is currently implemented in primary schools in Indonesia. This article aims to describe the implementation of the Pancasila Learner Profile Strengthening Project (P5) with the theme of Sustainable Lifestyle in Class IV of SDN Lamper Kidul 01. This research uses a qualitative method with a descriptive approach. The data collection technique was carried out by interviewing 3 resource persons, namely the Principal, the head of the P5 team and 2 grade IV students as participants in P5 activities. In implementing P5, students create or carry out a project. In its implementation, there are 2 stages, namely the conceptual stage and the contextual stage. The results showed that the implementation of the Pancasila Learner Profile Strengthening Project with the theme of Sustainable Lifestyle in class IV SDN Lamper Kidul 01 Semarang was carried out well and gained high enthusiasm from students. Through this P5 activity, it can foster and strengthen the dimensions of the Pancasila learner profile character in students, especially faith, devotion to God Almighty and noble character, mutual cooperation, independence, global diversity, critical reasoning, and creativity. Not only that, students also become literate and care about the surrounding environment.